Financial and legal principles of social protection of military personnel - O. P. Hetmanets (Bulletin of Kharkiv National University of Internal Affairs)
It has been proven that the legality and sufficiency of the state’s financial activities for the social protection of military personnel in modern conditions in Ukraine depends on financial and legal regulation in the field of social policy. It has been noted that financial and legal protection, as an activity of the state for financial provision of social protection of military personnel, is based on the budget law, expenditures, which require coordination of the budgetary powers of the legislator and the Government on the formation and distribution of financial resources at the planning stage, as well as development and approval of the main financial law.